LOSS GIVEN DEFAULT (LGD) KREDIT PEMILIKAN RUMAH (KPR) DI INDONESIA: ANALISIS MODEL INDUSTRI PERBANKAN DAN BANK BTN CABANG PURWOKERTO TAHUN 2002-2013 - Dian Pertiwi, Aisyah Oktasari; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2014)
Property industry drives economic activity by having a multiplier effect. On one hand the industry is pushing of economic activities in other sectors are related. On the other hand, excessive of property development industry can also have a negative impact for economy in case of oversupply and bubble pricing. Therefore in the lending activities bank must take security elements to minimize credit risk, such as Loss Given Default (LGD) or Severity of Loss.This research will analyze the factors that influence Loss Given Default (LGD) of loans mortgages in Indonesia during 2002-2013 using two models of research. LGD 1 models for Indonesian State Banks and LGD 2 models for sampled on BTN Bank Branch of Purwokerto.The results of this study indicate that there is no LGD on mortgages loans in both of the Indonesian state banks models or BTN Bank Branch of Purwokerto models. The property industry in Indonesia is unique among other countries as it offers a high return low risk investments. Property prices in Indonesia still stables despite high inflation and rising on interest rates. Based on the analysis, the Indonesian State Banks’s LGD influenced by House Price, Loan Amount, Growth BI Rate, and Growth GDP not significant. While at BTN Bank Branch of Purwokerto shows results that LTV, Unpaid Day, and Prime Lending Rate to be factors that influence the LGD.